Modified Brewster angle on conducting 2D materials. (30th January 2018) - Majérus, Bruno; Cormann, Mirko; Reckinger, Nicolas; Paillet, Matthieu; Henrard, Luc; Lambin, Philippe; Lobet, Michaël
Abstract: Insertion of two-dimensional (2D) materials in optical systems modifies their electrodynamical response. In particular, the Brewster angle undergoes an up-shift if a substrate is covered with a conducting 2D material. This work theoretically and experimentally investigates this effect related to the 2D induced current at the interface. The shift is predicted for all conducting 2D materials and tunability with respect to the Fermi level of graphene is evidenced. Analytical approximations for high and low 2D conductivities are proposed and avoid cumbersome numerical analysis of experimental data. Experimental demonstration using spectroscopic ellipsometry has been performed in the UV to NIR range on mono-, bi- and trilayer graphene samples. The non-contact measurement of this modified Brewster angle allows to deduce the optical conductivity of 2D materials. Applications to telecommunication technologies can be considered thanks to the tunability of the shift at 1.55 μ m.